A systematic review of multisensory cognitive–affective integration in schizophrenia. (August 2015) - Tseng, Huai-Hsuan; Bossong, Matthijs G.; Modinos, Gemma; Chen, Kuan-Ming; McGuire, Philip; Allen, Paul
Highlights: Multisensory integration (MSI) is a spontaneous perceptual–cognitive process. Deficits in MSI may hinder prompt and appropriate behavioural responses. MSI for non-emotional linguistic stimuli is impaired in schizophrenia. MSI for emotional stimuli in schizophrenia may also be altered. Functional alterations in temporal and frontal brain areas underlie MSI deficits. Abstract: The etymology of schizophrenia implies poor functional integration of sensory, cognitive and affective processes. Multisensory integration (MSI) is a spontaneous perceptual–cognitive process by which relevant information from multiple sensory modalities is extracted to generate a holistic experience. Deficits in MSI may hinder prompt and appropriate behavioural responses in a complex and transient environment. Despite extensive investigation of sensory, cognitive and affective processing in patients with schizophrenia, little is known about how MSI is affected in the illness. We systemically searched the PubMed electronic database and reviewed twenty-nine behavioural and neuroimaging studies examining MSI in patients with schizophrenia. The available evidence indicates impaired MSI for non-emotional stimuli in schizophrenia, especially for linguistic information. There is also evidence for altered MSI for emotional stimuli, although findings are inconsistent and may be modality-specific. Brain functional alterations in the superior temporal cortex and inferior frontal cortex appear to underlie the deficits in both non-emotional and emotional MSI. The limitations of the experimental paradigms used and directions for future research are also discussed.